(untitled) (Human Factors in Design, 2012)
The development of new and complex aircraft stimulates, more and more, the development of flight simulators. A flight simulator reproduces the dynamic model behavior of an aircraft, so the user can interact with the Simulator more realistically. Due to the relevance of the theme, the Group of Ergonomic Researches in Design of the Department of Design of UDESC carried out the project and mechanical production of a robotic platform with six degrees of freedom (6 DOF) for the study of a flight Simulator in immersive virtual reality. This study deals with the automation of the platform developed in order to make the movements of the flight simulator feasible in an environment of immersive virtual reality. With this purpose the technologies applied are described and the results achieved have been presented up to the present stage of development. The research envisages improving the standards of movement generated by flight simulators.